Alternative banking: theory and evidence from Europe - Kurt Von Mettenheim; Olivier Butzbach (Brazilian Journal of Political Economy, 2012)
Since financial liberalization in the 1980s, non-profit maximizing, stakeholder-oriented banks have outperformed private banks in Europe. This article draws on empirical research, banking theory and theories of the firm to explain this apparent anomaly for neo-liberal policy and contemporary market-based banking theory. The realization of competitive advantages by alternative banks (savings banks, cooperative banks and development banks) has significant implications for conceptions of bank change, regulation and political economy.